Population dynamics and projection methods - Stillwell, John C. H. (John Charles Harold) 1952-; Clarke, Marti Martin 1955- (Understanding population trends and processes, 2011)
Although the human population growth rate of the world has been  declining since peaking in the early 1960s, the populations of individual countries are changing at different rates.  Population dynamics at national level are partly determined by levels of fertility and mortality, but the impact of international migration is playing an increasingly important role. Moreover, internal migration plays a major part in population change at the sub-national level. This fourth volume in the series Understanding Population Trends and Processes is a celebration of the work of Professor Philip Rees. It contains chapters by contributors who have collaborated with Phil Rees on research or consultancy projects or as postgraduate students. Several chapters demonstrate the technical nature of population projection modelling and simulation methods while others illustrate issues relating to data availability and estimation. This book demonstrates the application of theoretical and modelling methods and addresses key issues relating to contemporary demographic patterns and trends